Oxidative insult can induce malaria-protective trait of sickle and fetal erythrocytes - Marek Cyrklaff (Nature Portfolio, 2016)
Carriers of haemoglobinopathies are protected from severe malaria, likely due to reduced surface expression of virulence factors. Here, Cyrklaff et al. show that, similar to haemoglobinopathies, a transient oxidative insult affects actin reorganization and mitigates the development of cerebral malaria in mice.